2002
DOI: 10.1523/jneurosci.22-16-07006.2002
|View full text |Cite
|
Sign up to set email alerts
|

AnIn VitroModel of Parkinson's Disease: Linking Mitochondrial Impairment to Altered α-Synuclein Metabolism and Oxidative Damage

Abstract: Chronic systemic complex I inhibition caused by rotenone exposure induces features of Parkinson's disease (PD) in rats, including selective nigrostriatal dopaminergic degeneration and formation of ubiquitin- and alpha-synuclein-positive inclusions (Betarbet et al., 2000). To determine underlying mechanisms of rotenone-induced cell death, we developed a chronic in vitro model based on treating human neuroblastoma cells with 5 nm rotenone for 1-4 weeks. For up to 4 weeks, cells grown in the presence of rotenone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
360
0
7

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 548 publications
(393 citation statements)
references
References 60 publications
26
360
0
7
Order By: Relevance
“…Of these five genes, ␣-Syn, parkin, and DJ-1 have been most intensively studied. Studies using in vivo animal models and in vitro cell culture have linked mutations of these genes to impairments of mitochondrial structure and function and oxidative stress response, reinforcing the general involvement of mitochondrial dysfunction and oxidative stress in PD pathogenesis (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Consistent with this notion, these proteins have been shown to be present in mitochondria or interact with mitochondrial proteins (8,(22)(23)(24), suggesting that they may directly regulate mitochondria function.…”
mentioning
confidence: 79%
“…Of these five genes, ␣-Syn, parkin, and DJ-1 have been most intensively studied. Studies using in vivo animal models and in vitro cell culture have linked mutations of these genes to impairments of mitochondrial structure and function and oxidative stress response, reinforcing the general involvement of mitochondrial dysfunction and oxidative stress in PD pathogenesis (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Consistent with this notion, these proteins have been shown to be present in mitochondria or interact with mitochondrial proteins (8,(22)(23)(24), suggesting that they may directly regulate mitochondria function.…”
mentioning
confidence: 79%
“…The damage reported in these studies was seen in the striatum first, followed by the SNpc (this is similar to the 'dying-back' phenomenon in PD); however, these changes were seen only in a subset of exposed animals. Additionally, increased oxidative stress, ubiquitin accumulation, proteasomal inhibition and inflammation all have been observed in response to rotenone exposure [19,[48][49][50]. Despite this evidence of a role for rotenone in PD pathogenesis, it is unlikely the rotenone is a major contributor because of its limited commercial use, short half-life in the environment and low bioavailability.…”
Section: Rotenonementioning
confidence: 99%
“…Dopamine deficiency and defects in mitochondrial complex I activity play important roles in the manifestation of PD (Javitch et al 1985;Parker et al 1989). Previous studies in humans and experimental animals have shown that 1-methyl-4-phenylpyridinium ion (MPP + ), the ultimate metabolic product of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), can induce PD-like symptoms (Lagnston et al 1983;Schmidt and Ferger, 2001;Sherer et al 2002). MPP + is taken into dopaminergic neurons and presumably other neurons and accumulates in the mitochondria, where it inhibits complex I activity.…”
Section: Introductionmentioning
confidence: 99%